2020
DOI: 10.1073/pnas.1915010117
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes upon gating of KirBac1.1 into an open-activated state revealed by solid-state NMR and functional assays

Abstract: The conformational changes required for activation and K+ conduction in inward-rectifier K+ (Kir) channels are still debated. These structural changes are brought about by lipid binding. It is unclear how this process relates to fast gating or if the intracellular and extracellular regions of the protein are coupled. Here, we examine the structural details of KirBac1.1 reconstituted into both POPC and an activating lipid mixture of 3:2 POPC:POPG (wt/wt). KirBac1.1 is a prokaryotic Kir channel that shares homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 81 publications
4
65
0
Order By: Relevance
“…To address the issue of peak overlap, in addition to 2D dipoleassisted rotational resonance (DARR; 12-ms, 25-ms, and 50-ms mixing times) and NcaCX and NcoCX spectra, we acquired three-dimensional (3D) CANcoCA (Cα-N-c′-C αi-1 ), NCACX (N i -Cα i -C i,sidechain ), and NCOCX (N i -C′ i-1 -C i-1,sidechain ) spectra. The signal to noise of these spectra was improved using double exponential weighted sampling and following protocols we and others previously reported (36,37). We assigned all backbone 15 N and 13 C and most sidechain resonances for 112 residues stretching from Q32 through V142, with limited ambiguity.…”
Section: Resultsmentioning
confidence: 99%
“…To address the issue of peak overlap, in addition to 2D dipoleassisted rotational resonance (DARR; 12-ms, 25-ms, and 50-ms mixing times) and NcaCX and NcoCX spectra, we acquired three-dimensional (3D) CANcoCA (Cα-N-c′-C αi-1 ), NCACX (N i -Cα i -C i,sidechain ), and NCOCX (N i -C′ i-1 -C i-1,sidechain ) spectra. The signal to noise of these spectra was improved using double exponential weighted sampling and following protocols we and others previously reported (36,37). We assigned all backbone 15 N and 13 C and most sidechain resonances for 112 residues stretching from Q32 through V142, with limited ambiguity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the SF tilt of GIRK2 is likely to affect the entrance of extracellular K + ions to the channel. Recently, a SSNMR study of KirBac1.1 has indicated that, the S4 binding site is expected to be involved in the conductive state of SF, and that deformation at S4 might refer to a nonconductive state [61] . Due to the homology between KirBac1.1 and Kir3.2, how the S4 binding site relates to the permeation efficiency through SF remains to be further clarified.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study over KirBac1.1 identified transmembrane residues with large CSPs in response to conformation exchange between the inactive and active states of the channel [65]. These residues are typically found near those known to be functional residues involved in conformational exchange within the transmembrane and extracellular regions and include both those observed in the inactive to active state transition and those found within alternate assignment pathways within the active state.…”
Section: Rare Codons In the Prokaryotic Transmembrane Regionmentioning
confidence: 99%